2007
DOI: 10.1590/s1413-70542007000300014
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de sementes de jenipapeiro submetidas à pré-embebição em regulador e estimulante vegetal

Abstract: RESUMOObjetivou-se avaliar a germinação de sementes e crescimento inicial de plântulas de jenipapo (Genipa americana L.) submetidas à pré-embebição em regulador e estimulante vegetal. Utilizou-se delineamento inteiramente casualizado com quatro repetições de 25 sementes e oito tratamentos, nos quais as sementes foram embebidas por 12 horas em: T1 -água, T2 Giberelina líquida a 4% de® a 10 mL L -1 . As sementes foram dispostas sobre folhas de papel toalha previamente umedecidas com água destilada e levadas para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
1
6
0
3
Order By: Relevance
“…The positive effect of Stimulate ® application on the germination speed has also been observed in soybean seeds (Moterle et al, 2011) and jeripape seeds (Prado Neto et al, 2007). Applying Stimulate ® in the production of soybean (Carvalho et al, 2013), bean (Abrantes et al, 2011), cowpea beans (Oliveira et al, 2015) and cotton (Silva et al, 2016) improved the vegetative development of these crops and increased the physicochemical quality of the grain, grain mass, yield and total dry biomass.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The positive effect of Stimulate ® application on the germination speed has also been observed in soybean seeds (Moterle et al, 2011) and jeripape seeds (Prado Neto et al, 2007). Applying Stimulate ® in the production of soybean (Carvalho et al, 2013), bean (Abrantes et al, 2011), cowpea beans (Oliveira et al, 2015) and cotton (Silva et al, 2016) improved the vegetative development of these crops and increased the physicochemical quality of the grain, grain mass, yield and total dry biomass.…”
Section: Resultsmentioning
confidence: 87%
“…Plant growth regulators can be applied by foliar spraying during cultivation, with the purpose of improving vegetative characteristics such as the physicochemical quality of the grain, grain mass, yield and total dry biomass (Abrantes et al, 2011;Carvalho, Viecelli, & Almeida, 2013;Silva, Santos, Oliveira, Soares, & Sanos, 2016). In seeds, plant growth regulators commonly used directly to improve germinative performance, prolong vigour and overcome physiological dormancy (Prado Neto, Dantas, Vieira, & Almeida, 2007;Moterle et al, 2011;Nonogaki, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments with distilled water and gibberellic acid in seeds (T1, T2, T3, T4, T5, T6, T7 and T8), provided the highest germination rate and speed values (from 80 to 91% and 0.80 to 0.91, respectively) ( Table 1), indicating that the form of GA3 application at the concentrations used did not influence the germination performance regardless of imbibition time even in water immersion or GA3 treatments. Prado-Neto et al (2007) observed positive effect of gibberellic acid at concentrations of 100 to 150 mL L -1 , and negative effect of biostimulant at concentration of 5 mL L -1 for the germination speed index in genipapo seeds (Genipa americana L.). The absorption of solutions by seeds must occur at rate that allows the repair and / or reorganization of membranes at appropriate levels to activate metabolism in phase I.…”
Section: Resultsmentioning
confidence: 92%
“…Growth regulating substances can act alone or in synergy with others (Prado-neto, et al, 2007). Currently, Stimulate® biostimulant compound is available on the market, which is composed of 0.009% kinetin (cytokinin), 0.005% gibberellic acid (gibberellin) and 0.005% indolbutyric acid (auxin).…”
Section: Introductionmentioning
confidence: 99%
“…(Nietsche et al, 2004), maracujá (Passiflora spp.) , pinha (Annona squamosa L.) (Wagner Júnior et al, 2006) e jenipapo (Genipa americana L.) (Prado Neto et al, 2007) foram secadas à sombra nos referidos trabalhos.…”
Section: Sementes Mortas (%) Ivgunclassified